High harmonic generation in mixed XUV and NIR fields at a free-electron laser. (7th January 2022) - Troß, Jan; Pathak, Shashank; Summers, Adam; Rompotis, Dimitrios; Erk, Benjamin; Passow, Christopher; Manschwetus, Bastian; Boll, Rebecca; Grychtol, Patrik; Bari, Sadia; Kumarappan, Vinod; Le, Anh-Thu; et al.
Abstract: We present the results of an experiment investigating the generation of high-order harmonics by a femtosecond near-infrared (NIR) laser pulse in the presence of an extreme ultraviolet (XUV) field provided by a free-electron laser (FEL), a process referred to as XUV-assisted high-order harmonic generation (HHG). Our experimental findings show that the XUV field can lead to a small enhancement in the harmonic yield when the XUV and NIR pulses overlap in time, while a strong decrease of the HHG yield and a red shift of the HHG spectrum is observed when the XUV precedes the NIR pulse. The latter observations are in qualitative agreement with model calculations that consider the effect of a decreased number of neutral emitters but are at odds with the predicted effect of the correspondingly increased ionization fraction on the phase matching. Our study demonstrates the technical feasibility of XUV-assisted HHG experiments at FELs, which may provide new avenues to investigate correlation-driven electron dynamics as well as novel ways to study and control propagation effects and phase matching in HHG.